On total asymptotically nonexpansive mappings in (Formula presented.) spaces - Bancha Panyanak (2018)
© 2014, Panyanak; licensee Springer. In this article, we obtain the demiclosed principle, fixed point theorems and convergence theorems for the class of total asymptotically nonexpansive mappings on (Formula presented.) spaces with (Formula presented.). Our results generalize the results of Chang et al. (Appl. Math. Comput. 219:2611-2617, 2012), Tang et al. (Abstr. Appl. Anal. 2012:965751, 2012), Karapınar et al. (J. Appl. Math. 2014:738150, 2014) and many others.